How do you solve 2x - (3/4) + (4/3) = 8 + (4/3)?

1 Answer
Jun 14, 2017

x = 4 3/8

Explanation:

2x - (3/4) + (4/3) = 8 + (4/3)

2x - (3/4) cancel(+ (4/3)) = 8 cancel(+ (4/3))

2x - (3/4) = 8

2x = 8 3/4

(color(red)(cancel(color(black)(2)))x)/color(red)(cancel(2)) = (8 3/4)/2

x = 35/4 ÷ 2/1

x = 35/4 xx 1/2

x = 35/8

color(blue)(x = 4 3/8

Now we can plug in this number to prove our answer.

2 xx 4 3/8 - (3/4) + (4/3) = 8 + (4/3)

8 3/4 - (3/4) + (4/3) = 8 + (4/3)

8 + (4/3) = 8 + (4/3)

8 4/3 = 8 + (4/3)

therefore 8 4/3 = 8 4/3